2020
DOI: 10.1039/d0ra08398d
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of PEG/mixed metal oxides as a new form-stable phase change material for thermoregulation and improved UV ageing resistance of bitumen

Abstract: As a new performance-enhancing additive, PEG/MMO PCM is expected to be effective in regulating extreme temperature and resisting UV aging of bitumen binder and thus could significantly extend the service life of bitumen pavement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 54 publications
2
11
0
Order By: Relevance
“…[47] The dope of Ag could also make SSPCM acquire catalytic properties. [48] Zhu et al [49] employed ZnMgAl-mixed metal oxides (MMO) matrix to impregnate PEG, the PEG/MMO SSPCMs with a PEG content of 65 wt.% acquired excellent shape stability and sufficient phase change enthalpy. Besides, the SSPCM exhibits considerate temperature regulation and aging resistance to the UV light, exhibiting potential of SSPCM novel applications.…”
Section: Metal Derivativesmentioning
confidence: 99%
“…[47] The dope of Ag could also make SSPCM acquire catalytic properties. [48] Zhu et al [49] employed ZnMgAl-mixed metal oxides (MMO) matrix to impregnate PEG, the PEG/MMO SSPCMs with a PEG content of 65 wt.% acquired excellent shape stability and sufficient phase change enthalpy. Besides, the SSPCM exhibits considerate temperature regulation and aging resistance to the UV light, exhibiting potential of SSPCM novel applications.…”
Section: Metal Derivativesmentioning
confidence: 99%
“…These properties are detailed in Table A1 , demonstrating their necessary roles in various applications. Also, as shown in Table A1 , the most frequently employed materials as PCM are polyethylene glycols, or PEGs, notably PEG2000 and PEG4000, due to their significant enthalpies during phase changes [ 12 , 13 , 25 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. These materials exhibit desirable attributes such as thermal and chemical stability, non-toxicity, and an appropriate phase change temperature range [ 44 ] during the phase change from solid.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is fundamental to investigate the thermal stability of PCM, which, in general, is performed using a thermogravimetric analyser. In addition, if the phase transition of the PCM in question is solid to liquid, it will probably be necessary to use a material that acts as a capsule or support for the PMC to prevent its leakage, which could even hurt the mechanical properties of the pavement [ 12 , 13 ]. In this case, the literature fundamentally presents two possibilities: (i) encapsulation (by melamine–formaldehyde resin [ 14 ], acrylic-based polymers [ 15 ], and CaCO 3 [ 16 ], among others) or (ii) impregnation using porous materials (silica fume [ 17 ], diatomite [ 18 ], expanded graphite, and others [ 19 ]) or crystalline/lamellar materials (expanded graphite [ 20 ], reduced graphene oxide [ 21 ], and montmorillonite [ 22 ] ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 13, it is observed that the C=O stretching vibration peak of the Q1 transparent flame‐retardant hydrogel sample at 1638 cm −1 becomes stronger, which corresponds to the hydrolysis of the amide group during the aging process, resulting in the decrease of the transmittance of the fireproof glass. However, the C=O stretching vibration peak of the Q2‐Q5 transparent flame‐retardant hydrogel samples only increases slightly, indicating that the PAM/PEG interpenetrating network structure is not easy to degrade under the UV radiation, which can improve the anti‐aging property of fireproof glass 27 . In addition, the O–H bending vibration peak of the Q2‐Q5 transparent flame‐retardant hydrogel samples at 1465 cm −1 is also enhanced, indicating that the hydrogen bond association in the Q2‐Q5 samples is stronger.…”
Section: Resultsmentioning
confidence: 99%